2003
DOI: 10.1088/0264-9381/20/21/006
|View full text |Cite
|
Sign up to set email alerts
|

Inertial forces and photon surfaces in arbitrary spacetimes

Abstract: Given, in an arbitrary spacetime (M, g), a 2-dimensional timelike submanifold Σ and an observer field n on Σ, we assign gravitational, centrifugal, Coriolis and Euler forces to every particle worldline λ in Σ with respect to n. We prove that centrifugal and Coriolis forces vanish, for all λ in Σ with respect to any n, if and only if Σ is a photon 2-surface, i.e., generated by two families of lightlike geodesics. We further demonstrate that a photon 2-surface can be characterized in terms of gyroscope transport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 14 publications
(33 reference statements)
1
44
0
1
Order By: Relevance
“…We have chosen the standard observers; a different choice would lead to different formulas for the inertial accelerations (19), (20) and (21), but to the same Ψ ± . For the sake of comparison, the reader may consult Nayak and Vishveshwara [20] where the inertial accelerations are calculated with respect to the zero angular momentum observers.…”
Section: Centrifugal and Coriolis Force In The Kerr-newman Spacementioning
confidence: 99%
“…We have chosen the standard observers; a different choice would lead to different formulas for the inertial accelerations (19), (20) and (21), but to the same Ψ ± . For the sake of comparison, the reader may consult Nayak and Vishveshwara [20] where the inertial accelerations are calculated with respect to the zero angular momentum observers.…”
Section: Centrifugal and Coriolis Force In The Kerr-newman Spacementioning
confidence: 99%
“…First we transport it along the curved projected trajectory, then we Lie-transport it up along the congruence as depicted in figure 1 3 . Alternatively, we may in the style of [4], consider the worldsheet spanned by the congruence lines that are crossed by the test particle worldline. On this sheet we can uniquely extend the forward vector t µ , defined along the test particle worldline, into a vector field that is tangent to the sheet, normalized and orthogonal to η µ .…”
Section: The Projected Curvature and Curvature Directionmentioning
confidence: 99%
“…These equations hold for all t and allt in R. By considering the special case t =t − R(t) we find R(t) = R t − 2R(t) (11) for allt in R. To ease notation, we drop the tilde in the following. By induction, (11) yields…”
Section: R(t) =R T − R(t)mentioning
confidence: 99%
“…Note that any timelike 2-surface is ruled by two families of lightlike curves; in general, however, these will not be geodesics. Foertsch, Hasse and Perlick [11] have shown that a timelike 2-surface is ruled by two families of lightlike geodesics if and only if its second fundamental form is a multiple of its first fundamental form. In the mathematical literature, such surfaces are called totally umbilic.…”
Section: Observer Fieldsmentioning
confidence: 99%
See 1 more Smart Citation